Analysis Of Dispute Resolution With Arbitration Measures Based On Law N0. 30 Year 1999 - Ahmad Muharrom; David Kurniawan; Dede Kurniawan (ISNU Sumatera Utara, 2024)
Dispute resolution through litigation often faces various obstacles, such as lengthy processes, relatively large costs, and lack of flexibility in meeting the needs of the parties. Therefore, arbitration is one of the alternative dispute resolution options that provides a more effective mechanism based on the principle of freedom of the parties. This study aims to analyze the position of arbitration and the stages of dispute resolution based on Law Number 30 of 1999 concerning Arbitration and Alternative Dispute Resolution. The research method used is normative juridical research with a statute approach and a conceptual approach. Research data was obtained through literature studies of legal regulations, literature, and doctrines related to arbitration and dispute resolution. The results of the study show that arbitration is a mechanism for resolving civil disputes outside the court which has special characteristics in the form of a process that is private, flexible, involves arbitrators who have certain expertise, and produces final and binding judgments. Based on Law No. 30 of 1999, dispute resolution is carried out through several stages, namely peace efforts between the parties, the assistance of mediators or expert advisors, and if no agreement is reached, it can be continued through arbitration institutions or ad hoc arbitration. In conclusion, arbitration is an effective dispute resolution mechanism because it is able to provide legal certainty, time efficiency, and protection of the interests of the parties in resolving civil disputes, especially in the field of trade.